Історичний досвід морально-психологічного забезпечення професійної діяльності у підрозділах рятувальників МНС України - Каретнік, І. М. (Видавництво Львівської політехніки, 2012)
Проаналізовано історичний досвід та комплекс практичних заходів щодо морально-психологічного забезпечення професійної діяльності у підрозділах рятувальників МНС України. The article is devoted to actual questions regarding peculiarities of moral and psychological ensuring of professional occupation of rescue units of Ministry of Emergencies of Ukraine. The conditions required for fruitful mutual service and education as well as dedicated and coordinated actions of subordinates to be engaged in educational process are clarified in the article.